Analysing the logistics impact on the cost composition of a mechanised spraying process of rendering mortar - Brandstetter, Maria Carolina Gomes de Oliveira; Carasek, Helena; Siqueira, Rainiere (Ambiente Construído, 2018)
The process of mortar mechanical projection has been approved in terms of its performance, but industrial management knowledge should be applied to understand the economic viability of the system. The aim of this paper is to evaluate the productivity and logistics impact of the mechanised spraying process of rendering mortar on its global cost composition. On a worldwide scale, there are no studies that correlate logistics, productivity and costs for mortar rendering systems, indicating the originality of the research. A multiple case study was proposed. A comparison was made between the manual application and mechanical projection methods of internal wall plastering. The data collection included identifying logistic bottlenecks, studying productive times, lead time, productivity, material consumption and losses and cost composition. The results showed that in both systems an impact on logistics occurs around 50% in teams´ productivity indices and global costs. The impact of productivity on indirect costs that reduce execution time and economic feasibility of the projection system is possible due to strategies that translate logistics efficiency.